In Search of Homo Economicus: Behavioral Experiments in 15 Small-Scale Societies - Henrich, Joseph; Boyd, Robert; Bowles, Samuel; Camerer, Colin; Fehr, Ernst; Gintis, Herbert; McElreath, Richard (American Economic Review, 2001)
In Search of Homo Economicus: Behavioral Experiments in 15 Small-Scale Societies by Joseph Henrich, Robert Boyd, Samuel Bowles, Colin Camerer, Ernst Fehr, Herbert Gintis and Richard McElreath. Published in volume 91, issue 2, pages 73-78 of American Economic Review, May 2001